PELATIHAN PENGEMBANGAN PROGRAM PEMBELAJARAN AKOMODATIF BAGI GURU DI SEKOLAH INKLUSIF DI KOTA MADIUN - Wagino Wagino; Hirnanda Dimas Pradana; Onny Fransinata Anggara (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
Teachers in education units providing inclusive education do not have enough competency to provide learning services for students with special needs. Therefore, short courses for teachers in schools providing inclusive education are urgently needed, especially in the City of Madiun. .Teachers in Madiun do not yet have adequate knowledge and skills in providing educational services for children with special needs in inclusive schools. The solution offered is through a technical guidance program for teacher competency development which is held in two procedures, namely participants carry out independent learning with the guidance of resource persons with a mentoring time of approximately 3 weeks and face-to-face learning which is carried out for 3 days and 2 nights. Furthermore, special supervising teachers and schools have difficulty accessing relevant learning resources related to accommodative learning. This resulted in teachers and school members not being able to optimally develop competencies in providing educational services for students with special needs in inclusive schools, so it is necessary to provide relevant modules to support the development of teacher competencies. This activity will be carried out for 5 months, covering the activities of Preparation, Implementation and Closing activities. It is hoped that from this activity the implementation of PKM will develop teacher competence to produce Bimtek modules and publication of articles on the effectiveness of the Bimtek program to improve teacher competency in schools in Madiun City.